Social and cultural determinants of antibiotics prescriptions: analysis from a public community health centre in North India - Mukherjee, Arunima; Surial, Rashmi; Sahay, Sundeep; Thakral, Yogita; Gondara, Amandeep (Frontiers in Pharmacology, 2024)
This paper explores the socio cultural and institutional determinants of irresponsible prescription and use of antibiotics which has implications for the rise and spread of antimicrobial resistance (AMR). This study describes the patterns of prescription of antibiotics in a public facility in India and identifies the underlying institutional, cultural and social determinants driving the irresponsible use of antibiotics. The analysis is based on an empirical investigation of patients’ prescriptions that reach the in-house pharmacy following an outpatient department (OPD) encounter with the clinician. The prescription analysis describes the factors associated with use of broad-spectrum antibiotics, and a high percentage of prescriptions for dental outpatient department prescribed as a precautionary measure. This paper further highlights the need for future research insights in combining socio-cultural approach with medical rationalities, to further explore questions our analysis highlights like higher antibiotic prescription, etc., Along with the recommendations for further research.